Soldier Recommendations for Improving Mental Health Treatment Seeking in the Military. (2nd April 2016) - Cheung, Janelle H.; Britt, Thomas W.; Raymond, Mary Anne; Zinzow, Heidi M.; Pury, Cynthia L. S.
ABSTRACT: Despite the prevalence of mental health issues in the military, only a minority of personnel who experience problems seek treatment. The underutilization of mental health services continues to be an important topic that deserves attention from both science and practice. Two studies were conducted with active-duty soldiers to assess their recommendations for actions that can be taken by soldiers who are experiencing mental health problems, their peers, their leaders, mental health professionals, and the upper-level chain of command to facilitate mental health treatment seeking. In addition, we compiled their recommendations to raise awareness, reduce stigma, and improve attitudes toward mental health treatment.